(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the role of color symbolism in the formation of national identity through a linguocultural perspective. The semantics of colors in various cultures, particularly in Uzbek and Spanish, and their reflection in phraseology are analyzed. The study follows the IMRAD methodology, allowing for a structured analysis of historical and cultural aspects of color perception, as well as the influence of religion and traditions on national color perception.